2021
DOI: 10.1002/ana.26280
|View full text |Cite|
|
Sign up to set email alerts
|

DBS of Thalamic Centromedian Nucleus for Lennox–Gastaut Syndrome (ESTEL Trial)

Abstract: Objective Prior uncontrolled studies have reported seizure reductions following deep brain stimulation (DBS) in patients with Lennox–Gastaut syndrome (LGS), but evidence from randomized controlled studies is lacking. We aimed to formally assess the efficacy and safety of DBS to the centromedian thalamic nucleus (CM) for the treatment of LGS. Methods We conducted a prospective, double‐blind, randomized study of continuous, cycling stimulation of CM‐DBS, in patients with LGS. Following pre‐ and post‐implantation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(97 citation statements)
references
References 36 publications
2
68
0
Order By: Relevance
“…34 Eighty-nine percent of the stimulation group had a ≥50% reduction in electrographic seizures relative to 0% of controls (odds ratio 23.25, 95% CI: 1.0-538.4, P = .05). 34 Most studies reported that <10% of patients experienced seizure freedom.…”
Section: Study-level Datamentioning
confidence: 93%
See 1 more Smart Citation
“…34 Eighty-nine percent of the stimulation group had a ≥50% reduction in electrographic seizures relative to 0% of controls (odds ratio 23.25, 95% CI: 1.0-538.4, P = .05). 34 Most studies reported that <10% of patients experienced seizure freedom.…”
Section: Study-level Datamentioning
confidence: 93%
“…As medications are typically unsuccessful at controlling seizures, disconnection procedures and vagus nerve stimulation have been used. 1a The recent Electrical Stimulation of Thalamus for Epilepsy of Lennox-Gastaut phenotype (ESTEL) trial investigated the benefits of centromedian nucleus deep brain stimulation (CMN DBS), building on efficaciousness reported in primarily case series 2a. However, analysis of these prior studies, which contain important clinical data and experience, has not been fully reported.…”
Section: Commentsmentioning
confidence: 99%
“…A prospective, randomized study of CM DBS in 20 patients with Lennox-Gastaut syndrome was recently reported, with 50% of the stimulation group achieving ≥50% seizure reduction, compared with 22% of controls. 6 In a recent retrospective case series of bilateral CM DBS in 12 patients with symptomatic generalized epilepsy (including Lennox-Gastaut syndrome) or IGE, 10 individuals achieved at least 50% decrease in seizure frequency at last follow-up. 7 Moving forward, it will be worthwhile to compare results with closed-loop responsive vs open-loop cycling CM stimulation in generalized epilepsies, although there is likely significant overlap in the mechanistic effects of these 2 stimulation paradigms.…”
Section: Commentarymentioning
confidence: 98%
“…Following the publication of promising reports [13], two RCTs were conducted in 1992 and 2000 showing some success for patients with Lennox-Gastaut syndrome and generalized tonic-clonic seizures [14,15]. Since then, CMT DBS has been investigated in multiple studies [16][17][18]. Notably, the electrical stimulation of thalamic centromedian nucleus for epilepsy of Lennox-Gastaut syndrome (ESTEL) trial, reported a reduction of electrographic seizures in patients with Lennox-Gastaut after CMT DBS [16].…”
Section: Thalamic Stimulation For Epilepsy: Earlier and Recently Inve...mentioning
confidence: 99%
“…Since then, CMT DBS has been investigated in multiple studies [16][17][18]. Notably, the electrical stimulation of thalamic centromedian nucleus for epilepsy of Lennox-Gastaut syndrome (ESTEL) trial, reported a reduction of electrographic seizures in patients with Lennox-Gastaut after CMT DBS [16]. Recently, a retrospective case series reported promising results with the combination of CMT and ATN DBS for the management of patients with generalized, multifocal, posterior origin and poorly localized drug-resistant epilepsy [17].…”
Section: Thalamic Stimulation For Epilepsy: Earlier and Recently Inve...mentioning
confidence: 99%